1989
DOI: 10.1136/bmj.298.6685.1423
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory studies of arthritis in leprosy.

Abstract: Seven renal abnormalities were diagnosed that had not been detected antenatally. Only one of the seven mothers had not attended for any scans; in the others the abnormality had not been found in appropriate scans. Four of these patients had vesicoureteric reflux, which is known to be difficult to diagnose antenatally. 4 The impact that early diagnosis of abnormalities of the fetal renal tract and subsequent intervention may have on the incidence of symptomatic renal disease later in life-for example, acute pye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 18 publications
0
22
0
2
Order By: Relevance
“…However, other studies have reported high frequencies of RF in leprosy, varying from 35 up to 60% (5,10,12,32). This discrepancy could be explained partially by a number of factors, including the type of assay utilized, study population, and possible role of different treatment regimens (31).…”
Section: Sle Ribeiro Et Almentioning
confidence: 63%
“…However, other studies have reported high frequencies of RF in leprosy, varying from 35 up to 60% (5,10,12,32). This discrepancy could be explained partially by a number of factors, including the type of assay utilized, study population, and possible role of different treatment regimens (31).…”
Section: Sle Ribeiro Et Almentioning
confidence: 63%
“…Rheumatological manifestations of leprosy involve skin, articular and soft tissues. 4 Arthritis predominantly involved the small joints of hands and resolved by 4 weeks in most patients. Type 1 lepra reaction usually manifests with exacerbation of the previously existing lesions.…”
Section: Discussionmentioning
confidence: 96%
“…8 However, Alcocer et al found arthritis in 12/18 (78%). 4 Two recent Indian studies observed the prevalence rates for arthritis in leprosy as 61.4% and 10%, respectively. 4 Two recent Indian studies observed the prevalence rates for arthritis in leprosy as 61.4% and 10%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactional states may present as acute or chronic polyarthritis. [26][27][28][29] Radiographies of the limbs in these patients reveal erosion and subluxation, 26 as well as phalangeal pseudocysts, collapse and cupping of joint surfaces. 3 Systemic manifestations may precede the appearance of cutaneous lesions, causing difficulties in diagnosis.…”
Section: Extracutaneous Manifestations and Laboratory Findingsmentioning
confidence: 99%